2012
DOI: 10.1126/scitranslmed.3003481
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Personalized in Vivo Analysis of Human Immune Responsiveness

Abstract: Personalized humanized mice can model intrinsic defects in human immune disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 48 publications
7
119
0
Order By: Relevance
“…On the same day, a piece of a partially HLA-matched cryopreserved and thawed fetal thymus was implanted under the kidney capsule of the animals. As previously shown, 10 human immune cells were detectable in PB 4 weeks after transplantation ( Figure 1A). B and T cells were the main human cell populations observed, with the former peaking around 10% of peripheral blood mononuclear cells (PBMCs) at week 12 and then slowly declining.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…On the same day, a piece of a partially HLA-matched cryopreserved and thawed fetal thymus was implanted under the kidney capsule of the animals. As previously shown, 10 human immune cells were detectable in PB 4 weeks after transplantation ( Figure 1A). B and T cells were the main human cell populations observed, with the former peaking around 10% of peripheral blood mononuclear cells (PBMCs) at week 12 and then slowly declining.…”
Section: Resultssupporting
confidence: 57%
“…Fetal thymus fragments were cryopreserved in 10% dimethyl sulfoxide (Sigma-Aldrich) and 90% human AB serum (Gemini Bio Products). 10 FL fragments were treated for 20 minutes at 37°C with 100 mg/mL of Liberase (Roche) to obtain a cell suspension. Human CD34 1 cells were purified from FL or BM by density gradient centrifugation (Histopaque-1077, Sigma) followed by positive immunomagnetic selection using anti-human CD34 microbeads (Miltenyi Biotec) according to the manufacturer's instructions.…”
Section: Animals and Human Tissues And Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalscheuer et al demonstrated that injection of human HSCs from bone marrow of adults, along with implantation of HLA-matched human fetal thymic tissue into immunodeficient mice, resulted in functional T cell, B cell, and myeloid cell reconstitution (36). Specifically, newly generated T cells were self tolerant and had a diverse repertoire.…”
Section: Finding the Perfect Castmentioning
confidence: 99%
“…38 Bone marrow analysis revealed that POM treatment significantly induced the formation of granulocyte/ macrophage progenitor cells (CD34…”
mentioning
confidence: 99%